Health beliefs and protection practices in the Hindu Community in Portugal - Ramos, Natália (2020)
The present study seeks to identify beliefs and protective practices used by Hindus residing in Portugal and to recognize how these beliefs and practices are perpetuated throughout the generations. It is a qualitative study in which semi-structured interviews, film observations and photographic observations were conducted, directed at the health and protection practices carried out in the temples and in the homes of Hindu families. The data collected in the interviews was subjected to content analysis and, through the images collected, practices related to health and protection were analysed. The results obtained reveal that Hindus initially resort to the practices transmitted by their ancestors in solving simpler health problems, demonstrating a strong connection with the culture of origin and respect and appreciation for the wisdom of the older members of the community. Intergenerational transmission is done informally through observation, the teaching of older elements and participation in rituals in a mutual recognition of ancient wisdom and the adaptive potential of younger people. It is mainly women who dominate health knowledge and practices and popular medicine.